Effect of phytase and zinc supplementation on growth performance,haemato-biochemical and carcass attributes in broiler chicken - PAL, ALOK; ALI, NAZIM; FAHIM, AHMAD; KUMAR, AMIT; SAHU, DS; ROY, DEBASHIS; VERMA, AKHILESH KUMAR; FAIZ, MOHD; SINGH, YASHESH (The Indian Journal of Animal Sciences, 2026)
The present study evaluated phytase supplementation with or without dietary zinc (Zn) on growth performance, feed utilization, blood bio-chemicals and carcass attributes of broiler chickens in a 5×3 randomized design. One hundred and eighty (180) day-old Cobb chicks were randomly divided in to fifteen groups of twelve in each and were allocated to five dietary treatments with three replications. The control group of chicks received a basal diet without phytase and Zn, wherein the treatment groups in addition to basal diet received phytase alone or phytase with Zn. The treatment group P600 received (phytase 600 U/kg feed), PZ640 (phytase 600 U/kg + Zn 40 mg/kg), P800 (phytase 800 U/kg), and PZ840 (phytase 800 U/kg + Zn 40 mg/kg) and were reared for five weeks under uniform management conditions. Results indicated that phytase supplementation (p < 0.01) improved body weight gain and feed conversion ratio (FCR) compared to the control treatment, with maximum improvement observed in the PZ840 group. Birds fed phytase with Zn exhibited superior growth and feed efficiency compared to phytase alone. Blood biochemical analysis revealed increased total protein, reduced uric acid, and elevated alkaline phosphatase (ALP) activity in phytase- and Zn-supplemented groups, indicating enhanced protein metabolism and mineral utilization. The present study concluded that the supplementation of phytase 800 U along with Zn 40mg per kg feed improved feed conversion ratio and growth performance in broilers chicks.